Optimizing the searching for H. pylori in clinical practice with EndoFasterⓇ. Issue 6 (June 2021) - Zullo, Angelo; Germanà, Bastianello; Galliani, Ermenegildo; Iori, Andrea; de Pretis, Giovanni; Manfredi, Guido; Buscarini, Elisabetta; Buonocore, Matteo Rossano; Monica, Fabio
Abstract: Background/Aim: H. pylori plays a major role in gastroduodenal diseases. Since its incidence is decreasing in developed countries, gastric biopsies were negative in several patients managed in clinical practice. We tested whether EndoFaster Ⓡ − a device allowing real-time H. pylori detection by gastric juice analysis – may optimize the need of biopsies. Methods: In this prospective, multicentre study, the accuracy of EndoFaster Ⓡ for H. pylori detection was computed by using histology of gastric biopsies as a gold standard. Results: Data of 525 consecutive patients were available, including 90 (17.1%) patients with infection. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy of EndoFaster Ⓡ were 87%, 84%, 53%, 97% and 85%, respectively. The overall accuracy of test was not affected neither by ongoing proton pump inhibitor therapy nor by previous eradication therapy. By using EndoFaster Ⓡ in our series, biopsy sampling could have been eventually avoided in a total of 279 patients, accounting for a reduction of 42.3%, accepting the risk of only 8 false negative cases. Conclusions: The very high NPV of EndoFaster Ⓡ might allow to safely halve the need of taking gastric biopsies in unselected patients managed in clinical practice, avoiding an unavailing consume of health resources.